2007
DOI: 10.1110/ps.062538707
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning protein pKavalues

Abstract: The ability to re-engineer enzymatic pH-activity profiles is of importance for industrial applications of enzymes. We theoretically explore the feasibility of re-engineering enzymatic pH-activity profiles by changing active site pK a values using point mutations. We calculate the maximum achievable DpK a values for 141 target titratable groups in seven enzymes by introducing conservative net-charge altering point mutations. We examine the importance of the number of mutations introduced, their distance from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…When reflects only the effect of electronic polarizability, values around 2 are used. When the reorganization of charges together with electronic polarizability is represented implicitly in the PBE model, the optimal value of can increase sometimes to values more than 20 [35,36].…”
Section: Pbe Solvers and The Protein Dielectric Constantmentioning
confidence: 99%
“…When reflects only the effect of electronic polarizability, values around 2 are used. When the reorganization of charges together with electronic polarizability is represented implicitly in the PBE model, the optimal value of can increase sometimes to values more than 20 [35,36].…”
Section: Pbe Solvers and The Protein Dielectric Constantmentioning
confidence: 99%
“…The polar nature of water molecules influences the structure of proteins, nucleic acids, and lipid membranes. The processes that shape such structures are in turn related to the solubilities of (biologically relevant) ions [8] and the propensity of acidic or basic biochemical groups to ionize in solution [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the pH dependence of protein stability and enzymatic activity is often determined by the pKa values of active-site residues [19,31]. When enzymes perform at high pH values, their acid/base residues have to maintain higher pKa values [12].…”
Section: Discussionmentioning
confidence: 99%